Effect of plant growth regulators on callus, cell suspension and cell line selection for flavonoid production from pegaga (centella asiatica L. urban) - Tan, Suat Hian; Musa, Radzali; Ariff, Arbakariya; Mahmood, Maziah (Science Publications, 2010)
Problem statement: Considering pegaga medicinal properties and over-exploitation, the requirement for a tissue culture technique as an alternative production system was crucial. Approach: Investigation of cell suspension culture response to different plant growth regulators (PRGs) for flavonoid production from elite cell line was carried out. Callus cultures were initiated from the leaf explants of Centella asiatica on Murashige and Skoog (MS) medium containing B5 vitamins and 30 g L−1 sucrose supplemented with different concentrations (0.5-2.5 mg L−1) of 2,4-D, NAA, Dicamba, Picloram and IBA supplied singly and in combination with different concentrations (0.5-1.5 mg L−1) of kinetin, BAP and TDZ. Results: Callus induction was observed for all the PGRs tested. The highest callus induction frequency (86.67%) was observed in MS medium containing 2.0 mg L−1 2,4-D while the combination of 2.0 mg L−1 2,4-D and 1 mg L−1 kinetin in MS medium gave the highest biomass yield (0.27 g dry weight culture−1). This combination was also found to be best for callus proliferation for all the accessions investigated. Among the four accessions tested, UPM03 was found to have the highest biomass yield (0.041 g DW culture−1) and hydrolysed flavonoid content (10.75 mg g−1 DW) after the 12th day of culture. The flavonoids present in the four accessions were quercetin, kaempherol, luteolin and rutin based on high performance liquid chromatography (HPLC) analysis. These results indicated that C. asiatica accession UPM03 was the potential elite cell line in mass production of flavonoid, especially luteolin. Coclusions/Recommendations: In the establishment of cell suspension culture, 2 mg L−1 2,4-D and 1 mg L−1 kinetin were the best PGRs in supporting the cell growth and flavonoid production. This is the first report on the use of PRGs on the establishment of cell suspension cultures in flavonoid production of C. asiatica.